2020
DOI: 10.1155/2020/3013029
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Atypical Facial Pain Caused by Eagle’s Syndrome

Abstract: Recurrent throat pain, “foreign body” sensation, difficulty in swallowing, or vague facial pain is many times caused by the presence of an elongated styloid process. Many times, this condition is misdiagnosed and the patient is treated for facial neuralgia. But once Eagle’s syndrome is confirmed by clinical and radiological examination, the treatment is always surgical resection. The approach maybe intraoral or extraoral. In this paper, we present a case of Eagle’s syndrome caused by bilateral elongation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
(10 reference statements)
0
9
0
1
Order By: Relevance
“…1 Eagle's syndrome is often misdiagnosed due to its rarity and non-specific symptoms, and delay to diagnosis has been reported to be between 10 and 27 years. 1,3,4 In our case report, it took almost an year for the patient to be diagnosed correctly. Similarly, it has been reported that despite that the patient having knowledge of Eagle's syndrome, it took 4 years to reach the correct diagnosis due to the unusual presentation of his symptoms.…”
Section: Case Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…1 Eagle's syndrome is often misdiagnosed due to its rarity and non-specific symptoms, and delay to diagnosis has been reported to be between 10 and 27 years. 1,3,4 In our case report, it took almost an year for the patient to be diagnosed correctly. Similarly, it has been reported that despite that the patient having knowledge of Eagle's syndrome, it took 4 years to reach the correct diagnosis due to the unusual presentation of his symptoms.…”
Section: Case Discussionmentioning
confidence: 73%
“…The styloid process is typically 20 to 30 mm in length, and patients with elongated styloid processes of 40 mm or longer have clinical distress 1,3 . This styloid process elongation could be unilateral or bilateral 4 . It affects around 4% of the general population, with 3:1 female predominance, however only 4% of these people experience associated symptoms 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] In addition, many studies have shown that symptoms occur when the styloid process is about 40 mm. [6] Watt W Eagle stated that about 4% of individuals whose length of the styloid process is >25 mm in adults could be symptomatic. [7] Godden et al reported that affected individuals with ES seldom develop symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of symptomatic ES in the general population is 0.16%, and only rare bilateral examples have been observed. 2,3 It is of additional interest that ES has recently been associated with hepatolineal (liver and spleen) fusion. 4,5 Because of the compact space in which the styloid presides, ES can present with a variety of manifestation.…”
Section: Pathology Clinicmentioning
confidence: 99%